IMPLEMENTING PROJECT-BASED LEARNING TO ENHANCE STUDENTS' ESSAY WRITING SKILLS (INTERNATIONAL SEMINAR, 2024)
This study explores the implementation ofProject-Based Learning (PBL) as an instructionalstrategy to enhance students' essay writing skills.The research was conducted in a secondaryeducation context, where students often strugglewith structuring ideas and maintaining coherence inessay writing. Through the PBL approach, studentsengaged in collaborative projects requiring them todraft, revise, and present essays based on real-worldtopics. Data collection involved pre- and post-tests,classroom observations, and student reflections toevaluate the effectiveness of the intervention. Thefindings revealed that PBL significantly improvedstudents' ability to organize ideas, developarguments, and express thoughts with clarity.Additionally, the collaborative aspect of PBLfostered a supportive learning environment thatencouraged peer feedback and critical thinking. Thisstudy concludes that PBL is an effective pedagogicalapproach to promote writing proficiency andrecommends its broader adoption in educationalsettings.